2019
DOI: 10.1377/hlthaff.2018.05060
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Of Practicing Physicians About Their Legal Obligations When Caring For Patients With Disability

Abstract: Disability civil rights laws require equitable treatment of the approximately sixty-one million Americans with disability. However, federal reports and numerous research studies indicate that this diverse and growing population often experiences health care disparities. To examine one possible contributing factor, we interviewed practicing physicians to explore their knowledge of their obligations to accommodate patients with disability under federal civil rights law. Interviewees reported having had little fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Simulated patients who were deaf at times received direction from clinic staff to bring a family member or friend to interpret for their appointment, which, unless there is an imminent threat to safety or welfare, does not comply with the Americans with Disabilities Act. 26 Although it has been demonstrated that health care professionals vary in their understanding of their legal responsibilities to patients with disabilities, 27 clinic staff may have engaged in explicit gatekeeping or discriminatory treatment of the SPs who were deaf. The VRS interpreters do not follow a scripted greeting, and some interpreters may have informed staff that a person who was deaf was calling or the staff person was able to surmise this based on background noise present during the call, since most VRS calls are made from a call center and present differently.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated patients who were deaf at times received direction from clinic staff to bring a family member or friend to interpret for their appointment, which, unless there is an imminent threat to safety or welfare, does not comply with the Americans with Disabilities Act. 26 Although it has been demonstrated that health care professionals vary in their understanding of their legal responsibilities to patients with disabilities, 27 clinic staff may have engaged in explicit gatekeeping or discriminatory treatment of the SPs who were deaf. The VRS interpreters do not follow a scripted greeting, and some interpreters may have informed staff that a person who was deaf was calling or the staff person was able to surmise this based on background noise present during the call, since most VRS calls are made from a call center and present differently.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to best practices that require the provision of reliable preventative and treatment advice, accessible information about COVID-19 (e.g., Braille, plain language, American Sign Language) has been neither immediately nor consistently available. Whether medical clinics and hospitals have adopted policies to assure accessibility of services and reasonable accommodations is unknown, but doubtful: Many health care facilities fail to provide such measures during regular times, due in part to clinicians' lack of knowledge and insufficient training in the needs and rights of people with disabilities (Agaronnik et al 2019;Sabatello 2019). These systemic deficiencies are further compounded for persons with disability who reside in congregate care settings.…”
Section: Disability Health Disparities and Covid-19mentioning
confidence: 99%
“…Many health care providers do not understand the requirements placed on them by the ADA and/or other communication access laws. 13 Health care providers report having little or no training on ADA requirements and demonstrate a failure to understand the basic tenets of disability civil rights law. 13…”
Section: Educating the Health Care Workforcementioning
confidence: 99%